PERILAKU KONSUMEN DALAM PEMBELIAN BAKSO DI PURWOKERTO - Rachmawati, Erny (Media Ekonomi, 2016)
Research on Consumer Behavior in Purchasing Meatballs in Purwokerto , the issue is what factors are dominating the consumer decision in purchasing meatballs in Purwokerto , so the purpose of this study are 1) to determine what factors are dominating the consumer decision in purchasing meatballs in Purwokerto , 2 ) to describe the factors of consumer behavior in purchasing meatballs in Purwokerto The research method used is descriptive qualitative with survey method using a questionnaire. Respondents were selected purposively work in productive age. Accidental sample data obtained. Collected data is displayed in tables and each factor in variables assessed percentage. The result, obtained a description that purchase meatballs in Purwokerto dominated by women aged between 16 to 25 years, the Islamic religion to the level of high school education and unmarried status. Respondents were mostly from outside Purwokerto with a length of stay of more than 10 years, and started eating the meatballs aged less than 10 years. Respondents obtain information where to sell meatballs comes from a friend. Typically, consumers buy meatballs in a stall, with a clean environment and has parking facilities. Assessment of marketing strategy, has the impression of a special taste factor making it easier for friends to draw consumer information. Meatballs is a food and culinary interlude, with the highest value of the visit comes from the arrival of the consumer with the family every month about 1 to 2times.Keywords : Meatballs, Consumer Behaviour , Purchasing Decision.